Crystal structures of 2, 3-bis(4-chlorophenyl)-1, 3thiazolidin-4-one and trans-2, 3-bis(4-chlorophenyl)-1, 3-thiazolidin-4-one 1-oxide. (March 2015) - Yennawar, Hemant P.; Tierney, John; Hullihen, Patrick D.; Silverberg, Lee J.
No abstract available